Age‐related differences in gut microbial community composition of captive spotted seals (Phoca largha). Issue 4 (10th August 2020) - Tian, Jiashen; Du, Jing; Han, Jiabo; Song, Xinran; Lu, Zhichuang
Abstract: Age is an important factor that significantly impacts the gut microbiota of various mammals. Captive spotted seals ( Phoca largha ) provide an ideal opportunity to study how age affects their gut microbiota, excluding other environmental factors, which is a challenge when monitoring wildlife. Here, the bacterial composition of the feces of captive spotted seals from four age groups were analyzed; namely, pup (<1 year old), juvenile (1–2 years old), subadult (2–3 years old), and adult (≥4 years old). Firmicutes were the dominant bacteria in all measured feces; however, the composition of gut microbiota in seals of different ages was distinct. Blautia, Slackia, and an unclassified Peptostreptococcaceae were more abundant in pups; Clostridium was abundant in juveniles; Fusobacterium, Bacteroides, and Psychrobacter were abundant in subadults; and Dorea and Peptostreptococcus abundant in adults. Two and 4 years of age appeared to be the most influential time nodes for variation in gut microbiota. In conclusion, this study identified age‐related differences in the composition of gut microbiota in P. largha .